PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PENGUNJUNG DI MUSEUM ADITYAWARMAN - Apriwanti, Nira; Silfeni, Silfeni; Suyuthie, Hijriyantomi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2016)
The purpose of this research is to examine the influence between the quality of service towards visitor satisfaction in Adityawarman Museum. The type of research is clausal assosiative. Population in this research are amounted to 117 people. The sampling technique is non probability sampling, by using insidental sampling. Sample in this research are amounted to 54 people. Data collecting using a questionnaire based on a Likert scale that has been tested for validity and reliability. Based on the results of theresearch concluded that in general about the quality of service in Adityawarman Museum is good (63 %), meanwhile for visitor satisfaction in Adityawarman Museum is also good (66,7 %). The results also indicate that the are significant influence between quality of service and visitor satisfaction in Adityawarman Museum with the coefficient determinant (R Square) value of 0,146 on a 0,004 significant value. Key Words: Quality of Service and Visitor Satisfaction